"Vi kan jo ikke gå hen og voldtage en mand, vel?" Om seksualiserede overgrebspersonlige og kønnede betydninger - Bodil Pedersen (The Royal Danish Library, 2008)
";We can't just rape a man right?"; - Gendered Personal Meanings of Sexualised Coercion. In mainstream psychological research, the experiences of women who have been subjected to sexualised coercion are frequently individualised and pathologised. But women's own perspectives indicate that personal meanings of coercion are reflected and changed in relation to their conduct of life. Their perspectives further our understanding of situated social reasons for changes in meanings attributed to - and actions related to - aspects of gender, sexualisation of appearance, and the conduct of intimacy and sexual life. They also point to the importance of further studies of the meanings of sexualised coercion.